1992
DOI: 10.1007/bf00051020
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic actions of tedisamil: Studies in rats and primates

Abstract: Tedisamil is a new bradycardic agent, previously shown to block transient outward and delayed rectifier potassium currents in cardiac tissue [1,2]. In the present study tcdisamil caused bradycardia and Q-Tc widening in rats and primates. Q-Tc widening is indicative of class III antiarrhythmic actions. In keeping with this, tedisamil had antiarrhythmic activity against electrical and ischemia-induced arrhythmias in rats. In rats, 0.5-4 mg/kg IV tedisamil caused parallel and dose-related increases in action-pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…In fact, tedisamil exerted At rest In animal studies, tedisamil showed a dose-dependent bradycardic effect [4,23,24]. In humans, Bargheer et al, in minimal and no significant bradycardic effect at the submaximal workload during exercise, while atenolol and 10 resting patients with coronary artery disease, observed that tedisamil (0.3 mg kg −1 i.v.)…”
Section: Analysis Of Qt Interval Prolongation Treatment Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, tedisamil exerted At rest In animal studies, tedisamil showed a dose-dependent bradycardic effect [4,23,24]. In humans, Bargheer et al, in minimal and no significant bradycardic effect at the submaximal workload during exercise, while atenolol and 10 resting patients with coronary artery disease, observed that tedisamil (0.3 mg kg −1 i.v.)…”
Section: Analysis Of Qt Interval Prolongation Treatment Comparisonsmentioning
confidence: 99%
“…However, the results of this study in healthy subjects An increase in action potential duration and a dosecannot be directly extrapolated to patients with ischaemic dependent QT interval prolongation have been shown heart disease. Further clinical studies in patients with during administration of tedisamil in animals studies [3, 4, myocardial ischaemia should be performed to confirm that 23,24]. In patients with coronary artery disease, Bargheer administration of tedisamil and a b-adrenoceptor blocker is et al observed a prolongation of the action potential not associated with an increase in unwanted cardiovascular duration and the ventricular effective refractory period [5].…”
Section: Tolerabilitymentioning
confidence: 99%
“…Prolongation of QT and QT c duration following tedisamil treatment, as an indicator of prolonged ventricular repolarization phase, may have an antiarrhythmic effect in patients with ischemia, as could be found in animal experiments [1,4,5]. Prolongation of QT, similar to Class I and III antiarrhythmic agents, contains the potential of a proarrhythmogenic effect with triggering of torsade de points and an increase in arrhythmogenic mortality.…”
Section: Mitrovic V Et Al Potassium Channel Openers and Blockers Inmentioning
confidence: 95%
“…It is known that tedisamil prolongs the actionpotential duration [17]. Two of the major effects on the heart, namely, bradycardia and prolongation of the action-potential duration, can both be explained by inhibition of outward potassium currents [18].…”
Section: Mechanism Of Increased Efticiency Of Workmentioning
confidence: 99%
“…The high heart rate and abnormally short action-potential duration of the rat heart, as well as the abnormally high external calcium used in this study, all constitute major reservations. Nonetheless, the combination of bradycardia and action-potential duration lengthening have been found not only in the rat but also in the baboon heart [17]. Bradycardia is likely to be protective from ischemia in all species, including humans, and the widened action-potential duration is likely to have antiarrhythmic qualities.…”
Section: Reservationsmentioning
confidence: 99%